Consumer-Driven Product Innovation Revolutionizes Indonesia's Snack Industry: Inovasi Produk Berbasis Konsumen Merevolusi Industri Makanan Ringan di Indonesia - Mubarok, Fajar Ibnu; Jakaria, Ribangun Bamban (Universitas Muhammadiyah Sidoarjo, 2024)
The research on consumer preferences for Sam Agung's tempe mendoan and spicy stuffed tofu products reveals significant insights into the desired product attributes. The conjoint analysis indicates that consumers prefer tempe mendoan with a slightly salty savory taste, a non-pungent aroma, a large shape, a soft texture, a half-cooked maturity level, paper box packaging, and a small logo. For spicy stuffed tofu, the preferred attributes include a sweet spicy taste, a non-pungent aroma, a round shape, a crispy texture, a mature maturity level, paper box packaging, and a small logo. These findings suggest that Sam Agung should consider these attributes for product improvement to align with consumer preferences, potentially enhancing customer satisfaction and sales. The importance values highlight critical attributes like the logo, shape, and maturity level for tempe mendoan, and taste, logo, and maturity level for spicy stuffed tofu. Future research could expand the sample size and explore additional product attributes or different market segments to further refine these insights and support broader applicability. Highlight: Consumer Preferences: Identified key attributes for tempe mendoan and spicy stuffed tofu. Conjoint Analysis: Used to determine and prioritize consumer preferences. Product Improvement: Suggested enhancements to better meet consumer demands. Keywoard: Consumer Preferences, Conjoint Analysis, Tempe Mendoan, Spicy Stuffed Tofu, Product Improvement